Lithium Preparations in Psychiatry, Addiction Medicine and Neurology. Part II. Biochemical Mechanisms of Its Action - R. A. Bekker (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Lithium is the first and the lightest in the series of alkali metals, to which, in addition to lithium, two very biologically important elements – sodium and potassium, as well as trace elements rubidium and cesium, belong. Despite its formal affiliation to the group of alkali metals, lithium, like many other chemical elements of the «atypical» second period of the periodic table (for example, boron), is more similar in its chemical properties not to its counterparts in the group, but to its «diagonal brother» – magnesium. As we will show in this article, the diagonal chemical similarity between lithium and magnesium is of great importance for understanding the mechanisms of its intracellular biochemical action. At the same time, the intragroup chemical similarity of lithium with sodium and potassium is more important for understanding the mechanisms of its absorption, its distribution in the body and its excretion. Despite the 70 years that have passed since John Cade’s discovery of the antimanic effect of lithium, the mechanisms of its therapeutic action are still not completely understood. In the end, it turns out that the mechanism of the therapeutic action of lithium is extremely complex, multicomponent, unique and not imitable. Certain aspects of the mechanism of its action may be compatible with the mechanisms of action of other mood stabilizers, or with the mechanisms of action of so-called «lithium-mimetics», such as ebselen. However, no other drug to date failed to fully reproduce the biochemical effect of lithium on the body.